Exploring the effects of habit strength on scholarly publishing. Issue 6 (30th June 2020) - Moksness, Lars; Olsen, Svein Ottar; Tuu, Ho Huy
Abstract : Purpose: This study aims to explore the role of habit strength in explaining intention and open access (OA) and non-OA scholarly publishing. Design/methodology/approach: A decomposed theory of planned behaviour (TPB) is used as the conceptual framework to investigate a sample of 1, 588 researchers from the major universities in Norway. Different latent construct models are analysed with a structural equation modelling approach. Findings: The results show that the effect of habit was non-significant in an extended TPB framework where attitude was most important, followed by norms and perceived behavioural control in explaining intention to submit OA. Habit was only found to have a significant impact on intention to submit OA when it played a role as a full mediator for the effects of the intentional antecedents. In this modified model, norms were found to have a stronger effect than attitudes in explaining the habit to submit OA. OA habit strength forms intentions to publish in OA journals and reduces the intention to publish and publishing behaviour in NOA journals. Research limitations/implications: Other individual forces (e.g. personality and personal values) and the role of habit strength should be included for future research. Practical implications: The results provide empirical insights to management, policy makers and research on scholarly publishing. Originality/value: This paper contributes not only to the understanding of OA scholarly publishing, but is also relevant for research on what drives (academic) data sharing, knowledge sharing, the sharing economy or the open source movement.